2022
DOI: 10.1002/jcop.22926
|View full text |Cite
|
Sign up to set email alerts
|

“I left my shyness behind”: Sustainable community‐led development and processes of motivation among rural Nicaraguan women

Abstract: This paper explores motivational changes of Nicaraguan women involved in sustainable community‐led development. Sustainability is the goal of many organizations engaged with capacity development interventions. Research on what such sustainability entails point to a correlation between sustained action by communities, postintervention, and high levels of social capital, collective agency, and efficacy. But what factors motivate people to develop the social capital, self‐efficacy, and agency that enable them to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…These results are consistent with several studies that have explored the role of gender in agricultural projects. Cloete et al ( 55 ) found that rural Nicaraguan women’s motivations change from initial to sustained forms, enabling them to sustain community-led projects and build social capital, self-efficacy, and agency. Amran and Fatah ( 56 ) studied women’s empowerment in agriculture in Malaysia and found that access to extension services and effective decision-making are key factors, but limited leadership, motivation and engagement challenges, and restricted community group participation hinder women’s empowerment.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with several studies that have explored the role of gender in agricultural projects. Cloete et al ( 55 ) found that rural Nicaraguan women’s motivations change from initial to sustained forms, enabling them to sustain community-led projects and build social capital, self-efficacy, and agency. Amran and Fatah ( 56 ) studied women’s empowerment in agriculture in Malaysia and found that access to extension services and effective decision-making are key factors, but limited leadership, motivation and engagement challenges, and restricted community group participation hinder women’s empowerment.…”
Section: Resultsmentioning
confidence: 99%